Four-week pedometer-determined activity patterns in normal-weight, overweight and obese adults - Stacy Clemes; Sarah L. Hamilton; Martin Lindley (2008)
OBJECTIVE: To assess pedometer-determined ambulatory activity in normal-weight, overweight and obese UK adults. METHODS: 86 normal-weight (BMI